2021
DOI: 10.3390/cells10051114
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cells in Chronic Hepatitis B and T Cell-Directed Immunotherapy

Abstract: The impaired T cell responses observed in chronic hepatitis B (HBV) patients are considered to contribute to the chronicity of the infection. Research on this impairment has been focused on CD8+ T cells because of their cytotoxic effector function; however, CD4+ T cells are crucial in the proper development of these long-lasting effector CD8+ T cells. In this review, we summarize what is known about CD4+ T cells in chronic HBV infection and discuss the importance and opportunities of including CD4+ T cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 101 publications
2
25
0
Order By: Relevance
“…Dysfunctional CD4 + T cells are closely correlated with the upregulation of immune co-inhibitory molecules expressed on CD4 + T cells that usually played an immunosuppressive function, such as TIM-3, PD-1, LAG-3, and CTLA-4 ( Park et al, 2016 ; Salimzadeh et al, 2018 ; Dong et al, 2019 ; Fisicaro et al, 2020 ; Ferrando-Martinez et al, 2021 ). Previous reports showed an increased frequency of PD-1 + CD4 + T cells, TIM-3 + CD4 + T cells, LAG-3 + CD4 + T cells, and CTLA-4 + CD4 + T cells in chronic HBV infection, and the blockade of the co-inhibitory receptors contributed to the restoration of CD4 + T cell proliferation and function and promoted cytotoxic effector of CD8 + T cells that played critical roles in viral clearance and disease pathogenesis of sustained HBV infection ( Peng et al, 2008 ; Dong et al, 2017 , 2019 ; Buschow and Jansen, 2021 ; Xiong et al, 2021 ). However, these studies did not display detailed data on ASCs of patients with chronic HBV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysfunctional CD4 + T cells are closely correlated with the upregulation of immune co-inhibitory molecules expressed on CD4 + T cells that usually played an immunosuppressive function, such as TIM-3, PD-1, LAG-3, and CTLA-4 ( Park et al, 2016 ; Salimzadeh et al, 2018 ; Dong et al, 2019 ; Fisicaro et al, 2020 ; Ferrando-Martinez et al, 2021 ). Previous reports showed an increased frequency of PD-1 + CD4 + T cells, TIM-3 + CD4 + T cells, LAG-3 + CD4 + T cells, and CTLA-4 + CD4 + T cells in chronic HBV infection, and the blockade of the co-inhibitory receptors contributed to the restoration of CD4 + T cell proliferation and function and promoted cytotoxic effector of CD8 + T cells that played critical roles in viral clearance and disease pathogenesis of sustained HBV infection ( Peng et al, 2008 ; Dong et al, 2017 , 2019 ; Buschow and Jansen, 2021 ; Xiong et al, 2021 ). However, these studies did not display detailed data on ASCs of patients with chronic HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that high expressions of immune checkpoint molecules (TIM-3, PD-1, CTLA-4, and LAG-3) on CD4 + T cells are related to decreased secretion of cytokines and proliferation capacity of T cells, such as IFN-γ + Th1, IL-4 + Th2, IL-17A + Th17, and IL-21 + Tfh cells, except for PD-1 high Tfh cells that have the capacity of inducing B-cell response and the generation of specific antibodies against antigens or viruses ( Gibney et al, 2016 ; Park et al, 2016 ; Saeidi et al, 2018 ; Buschow and Jansen, 2021 ). However, Treg cells with increased expressions of immune checkpoint molecules displayed a high immunosuppressive function on HBV-specific Th1 and Tfh responses and promoted IL-10 and TGF-ß1 secretion ( Stoop et al, 2005 ; Buschow and Jansen, 2021 ). This study showed that the frequencies of circulating TIM-3 + or PD-1 + Tfh cells and TIM-3, LAG-3, and PD-1 molecules on Th1, Th2, Th17, and Treg cells were significantly expanded in chronic ASCs with HBeAg-negative in comparison with HC, which were partially accordant with previous reports ( Stoop et al, 2005 ; Wang R. et al, 2018 ; Wang X. et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the inclusion and exclusion criteria used in this study, patients with chronic persistent human immunodeficiency virus, hepatitis C virus, and human papilloma virus infections were excluded. Although it is not well-understood whether hepatitis B can cause CD4 + T cell depletion, the immune mechanism of patients with progressive damage due to chronic infection is clear ( 31 , 32 ). However, as many patients have chronic hepatitis B infection, they are not suitable for direct exclusion; therefore, we conducted subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, timing for the succession of different combined interventions needs to be well calibrated: first the viral antigenic burden, including HBeAg, should be reduced by antiviral treatments, then therapeutic vaccination could be considered associated with a Th1 skewing adjuvant, before or after T cell-enhancing drugs. Finally, antiviral therapy suspension can also function as a natural booster, eventually resulting in infected hepatocyte clearance [ 8 ].…”
mentioning
confidence: 99%